Development of a Validated Bioanalytical UPLC–MS/MS Method for Quantification of Neratinib: A Recent Application to Pharmacokinetic Studies in Rat Plasma. (6th July 2021) - Alrobaian, Majed; Panda, Sagar Suman; Afzal, Obaid; Kazmi, Imran; Alossaimi, Manal A; Al-Abbasi, Fahad A; Almalki, Waleed H; Soni, Kriti; Alam, Ozair; Alam, Md Naushad; Rub, Rehan A; Rahman, Mahfoozur; et al.
Abstract: Neratinib, a tyrosine kinase inhibitor, was very recently approved by USFDA in 2017 as an anticancer drug to treat of HER2 positive breast cancers. The present work provides an account on the development of a validated bioanalytical UPLC–MS/MS method for quantification of neratinib and internal standard (imatinib) in rat plasma and tissue homogenates. A UPLC having a 100 mm C18 column (1.7 μm sized particles) was used with acetonitrile (0.1% formic acid): 2 mMol of ammonium acetate in water (pH 3.5) as the mobile phase. An efficient chromatographic separation was performed and detection was achieved by monitoring precursor-to-product ion transitions with m/z 557.29 → 112.06 for neratinib and m/z 494.43 → 294.17 for IS. The method demonstrated excellent linearity in the spiked plasma drug concentrating ranging between 1 and 800 ng.mL −1 (r 2  = 0999), with lower limit of quantification (LLOQ) was observed at 1 ng.mL −1 . Intra-assay and inter-assay precision relative standard deviations were found to be within 6.58. Mean extraction recovery for neratinib and IS were 99.44 and 99.33%, while matrix effect for neratinib and IS was ranging between −4.35 and − 3.66%, respectively. Overall, the method showed successful applicability in pharmacokinetic analysis of pure various formulations in Wistar rat plasma.